Determination of Acrylamide in Portuguese Bread by UPLC-MS/MS: metrological and chemometric tools - Jesus, Susana (2019)
Acrylamide (AA) is known for its potential health hazards and it is present in processed potatoes, coffee, and bread. Wheat is still the most important cereal for bread making, however, the interest in its substitution by other grains is growing due to the consumer demand for novels and healthy foods, like oat and rye flour. The aim of this study was to analyze the AA content of confectioned bread in fifty-four different pastries and make an association of acrylamide contents and the place of production to identify the quality of the flour used. There was a wide variability in AA levels among different breads and within different bread varieties. The median of AA values was 787 μg/kg for whole grain bread, 783 μg/kg for oat bread and 253 μg/kg in rye bread. With the cluster analysis, it was possible to conclude that besides the factors like baking temperature-time and fermentation time which affects AA formation in bread products, several other parameters such as the formulation, flour quality and the varieties of processing techniques, among others, play a crucial role in the AA formation.